2023
DOI: 10.3748/wjg.v29.i21.3241
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of the gut microbiome in post-infectious irritable bowel syndrome: A literature review

Abstract: Post-infectious irritable bowel syndrome (PI-IBS) is a particular type of IBS, with symptom onset after an acute episode of infectious gastroenteritis. Despite infectious disease resolution and clearance of the inciting pathogen agent, 10% of patients will develop PI-IBS. In susceptible individuals, the exposure to pathogenic organisms leads to a marked shift in the gut microbiota with prolonged changes in host-microbiota interactions. These changes can affect the gut-brain axis and the visceral sensitivity, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 120 publications
0
21
0
2
Order By: Relevance
“…Once the infection is treated and inflammation subsides, the gut microbiota tends to recover and return to its pre-infection state. However, in some cases, the infection and associated inflammation can cause lasting changes to gut microbiota composition, provoking symptoms that are categorized as post-infectious irritable bowel syndrome and may include abdominal discomfort, bloating, and alternation between diarrhea and constipation [ 157 ]. It is important to note that the exact mechanisms underlying the relationship between gut inflammation and gut microbiota are still being studied.…”
Section: Exploring the Role Of Probiotics In Managing Intestinal Dise...mentioning
confidence: 99%
“…Once the infection is treated and inflammation subsides, the gut microbiota tends to recover and return to its pre-infection state. However, in some cases, the infection and associated inflammation can cause lasting changes to gut microbiota composition, provoking symptoms that are categorized as post-infectious irritable bowel syndrome and may include abdominal discomfort, bloating, and alternation between diarrhea and constipation [ 157 ]. It is important to note that the exact mechanisms underlying the relationship between gut inflammation and gut microbiota are still being studied.…”
Section: Exploring the Role Of Probiotics In Managing Intestinal Dise...mentioning
confidence: 99%
“…The relationship between the intestinal microbiome and multiple systemic pathologies such as atopy (asthma), autoimmunity (SLE, celiac disease) or even post-infectious irritable bowel syndrome is well known. In the case of SLE, the presence of autoimmunity is marked at the intestinal level mainly by a low Firmicutes - Bacteroidetes ratio, together with an increase in Prevotella, Rhodococcus, Eggerthella and Klebsiella ( 35 39 ). Vitamin D3 also exerts effects on the integrity of the intestinal barrier, the bacterial translocation capacity and the microbial balance, thus revealing another way through which it can mediate interactions with the host’s immune system, imprinting the pathogenesis of SLE ( 35 ).…”
Section: Pathogenesis Of Psle From the Perspective Of Hypovitaminosis Dmentioning
confidence: 99%
“…These environmental factors may trigger dysbiosis, leading to increased vulnerability of the child’s intestine to Shigella species. A recent review showed that while the exact mechanisms are still not entirely clear on how post-infectious irritable bowel syndrome (PI-IBS) starts, alterations in gut microbiota, immune responses, and gut-brain interactions likely contribute to the development of PI-IBS [ 117 ], suggesting the connection between microbiota and PI-IBS.…”
Section: Intestinal Microbiota In Health and Diseasementioning
confidence: 99%